Type B thymomas in patients with myasthenia gravis display a distinctive pattern of αβ TCR and IL-7 receptor α expression on CD4+CD8+ thymocytes - Tianlai Wang; Boyu Wang; Xiaowu Fan; Yixin Cai; Lequn Li; Shengling Fu (Autoimmunity)
Thymoma is closely associated with myasthenia gravis (MG). However, due to the heterogeneity of thymoma and the intricate pathogenesis of MG, it remains unclear why some patients with thymoma develop MG and others do not. In this study, we conducted a comparative phenotype analysis of thymocytes in type B thymomas in patients with MG (MG (+) thymomas) and without MG (MG (−) thymomas) via fluorescence-activated cell sorting (FACS). Our results show that the developmental stages defined by the expression of CD3, CD4, and CD8 were largely maintained in both MG (+) and MG (−) thymomas, with CD4+CD8+ cells constituting the majority of thymocytes in type B thymoma, and no significant difference between this cell population was observed in MG (+) and MG (−) thymomas.We discovered that CD4+CD8+ thymocytes in MG (+) thymomas expressed low levels of αβ TCR and high levels of IL-7 receptor α (IL-7Rα), whereas in MG (−) thymomas, CD4+CD8+ thymocytes exhibited the opposite pattern of αβ TCR and IL-7Rα expression. These results suggest that the positive and negative selection processes of CD4+CD8+ thymocytes might differ between MG (+) thymomas and MG (−) thymomas. The expression of the Helios transcription factor is induced during negative selection and marks a group of T cells that have undergone negative selection and are likely to be deleted due to strong TCR binding with self-peptides/MHC ligands. We observed that the percentage of Helios-positive CD4SP T cells was greater in MG (−) than in MG (+) thymomas. Thus, the differentially regulated selection process of CD4+CD8+ thymocytes, which involves TCR and IL-7/IL-7Rα signaling, is associated with the presence of MG in type B thymomas.